BEHAVIOR DETERMINANTS OF STUNTING PREVENTION INADOLESCENT GIRLS IN THE TIDORE ISLANDS - Osnawati Marsaoly; Arif Mustofa; Sulastri Marapil (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
Stunting is a chronic nutritional problem that remains a national concern because it impacts the quality of human resources in the future. Adolescent girls play a crucial role in stunting prevention efforts, as they are potential mothers who play a role in creating a healthy generation. This study aims to analyze factors related to stunting prevention behavior in adolescent girls at State Senior High School 5 Tidore Islands. This study was quantitative with a cross-sectional design. The study population included all 274 female students at State Senior High School 5 Tidore Islands, with a sample of 73 students taken using a simple random sampling technique. Data were collected using a questionnaire that had been tested for validity and reliability. The results showed a significant relationship between knowledge (p = 0.000), attitude (p = 0.000), and social environment (p = 0.000) with stunting prevention behavior. The Odds Ratio (OR) value for knowledge was 17.409; attitude 31.963; and social environment 19.419. The conclusion of this study is that the better the knowledge, attitudes, and social environment of adolescent girls, the better their behavior in preventing stunting.